End-user programming architecture facilitates the uptake of robots in social therapies - Barakova, E.I.; Gillesen, J.C.C.; Huskens, B.E.B.M.; Lourens, T. (Robotics and autonomous systems, 2013)
This paper proposes an architecture that makes programming of robot behavior of an arbitrary complexity possible for end-users and shows the technical solutions in a way that is easy to understand and generalize to different situations. It aims to facilitate the uptake and actual use of robot technologies in therapies for training social skills to autistic children. However, the framework is easy to generalize for an arbitrary human–robot interaction application, where users with no technical background need to program robots, i.e. in various assistive robotics applications. We identified the main needs of end-user programming of robots as a basic prerequisite for the uptake of robots in assistive applications. These are reusability, modularity, affordances for natural interaction and the ease of use. After reviewing the shortcomings of the existing architectures, we developed an initial architecture according to these principles and embedded it in a robot platform. Further, we used a co-creation process to develop and concretize the architecture to facilitate solutions and create affordances for robot specialists and therapists. Several pilot tests showed that different user groups, including therapists with general computer skills and adolescents with autism could make simple training or general behavioral scenarios within 1 h, by connecting existing behavioral blocks and by typing textual robot commands for fine-tuning the behaviors. In addition, this paper explains the basic concepts behind the TiViPE based robot control platform, and gives guidelines for choosing the robot programming tool and designing end-user platforms for robots. ► Programming architecture to help end-users create interactive scenarios is proposed. ► Complex programming concepts are explained for non-programmers. ► Iterative co-creation process leads to robot scenarios for training autistic children. ► Using TiViPE therapists can create interactive robot behaviors within 1 h. ► The architecture facilitates creation, and sharing of robot training scenarios.